Venice privileges in the Arab Orient - Sallat, Aiman (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The study deals with the question of the privileges of Venice in the Arabic Orient and the development of these privileges in the Ottoman period, by understanding the meaning of the privileges and their historical development in the Ottoman Empire and the circumstances that accompanied the granting of economic, religious and judicial privileges to the Venetians, exploited by them to achieve their interests and expand their trade. The study also deals with the Treaty of 1517 between the Ottomans and the Venetians as an example of the positive and negative effects on both sides. This treaty is considered the basis for subsequent treaties between the Ottomans on the one hand and the Venetians and the European countries on the other.